The role of fractures and dislocations and the recognition of traumatic findings in classical Ottoman medicine - Aslan Aydoğdu, Zehra; Altıntaş, Ayten (The Bulletin of Legal Medicine, 2025)
Objective: In our study, we aim to contribute to the fields of Medical History and Forensic Medicine by comparatively analyzing the descriptions of bone fractures and dislocations, their mechanisms, and healing durations found in Ottoman-era medical texts. Methods: For this study, 93 Ottoman-era medical books were examined as sources. Among the examined books, two were identified as containing information on fractures and dislocations that are significant from a forensic medical perspective. Results: Some general descriptions related to fractures in these works include statements such as: “If the bone has not shifted, no sound is produced, and there is no pain during examination; in this case, the bone is not fractured but rather bruised, cracked, or slightly split.” The causes of fractures are described as resulting from falling from a height, being struck by wood, stone, flat arrows, swords, cannonballs, muskets, or from other similar impacts. Although modern medicine recognizes numerous factors influencing bone healing times, these historical texts mention that the healing period for a femur fracture is 50 days. Regarding dislocations, it is stated that elbow dislocations do not occur with minor force and are difficult to reposition, while various other details relevant to forensic medicine are provided for other types of dislocations. Conclusion: The examination of these sources reveals that Ottoman medical scholars possessed considerable knowledge regarding fractures and dislocations. These findings provide insight into the knowledge and practices of Ottoman-era physicians in the context of trauma and forensic evaluation.